Multicenter, cross-sectional observational study of the impact of neuropathic pain on quality of life in cancer patients - Oh, So Yeon (Support Care Cancer, 2017)
PURPOSE: Neuropathic cancer pain (NCP) is a common and potentially debilitating symptom in cancer patients. We investigated the prevalence of NCP, as well as its management and association with QOL. METHODS: Cancer patients with pain ≥1 on the visual analogue scale (VAS) were surveyed with the Douleur Neuropathique (DN4) questionnaire, the Brief Pain Inventory-Short Form (BPI-SF), and the EuroQOL five dimensions (EQ-5D) questionnaire. The associations between NCP and pain severity or NCP and QOL, while controlling for variables relevant to QOL, were then analyzed. RESULTS: A total of 2003 patients were enrolled in this survey; the prevalence of NCP was 36.0% (n = 722, 95% CI, 32.5–39.5). We found that NCP in cancer patients was closely correlated to a higher pain severity (BPI-SF; 4.96 ± 1.94 versus 4.24 ± 2.02, p < 0.001), and in patients with NCP, pain more severely interfered with daily living, as compared to those without NCP (BPI-SF; 4.86 ± 2.71 versus 4.41 ± 2.87, p < 0.001). Patients with NCP also had worse QOL than those without NCP, as measured by EQ-5D index score (0.47 ± 0.30 vs. 0.51 ± 0.30, p = 0.005), and this was confirmed using multivariate analysis (p < 0.001), even after controlling for other variables such as age, sex, disease stage, cancer duration, radiotherapy, chemotherapy, and comorbidities. Importantly, adjuvant analgesics were used in less than half of patients with NCP (n = 358, 46.4%). CONCLUSIONS: We found that NCP in cancer patients was significantly associated with a worsened QOL, and current management is inadequate. Therefore, future research aimed at developing improved strategies for management of NCP is required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00520-017-3806-5) contains supplementary material, which is available to authorized users.